ANALYSIS OF FACTORS AFFECTING THE LEVEL OF HARVEST PREMIUMS ON OIL PALM HARVEST EMPLOYEES PT. AGRO SINERGI NUSANTARA BATEE PUTEH PLANTATION AFDELING I - Dodi Setiawan; Bagio; Teuku Athaillah; Qhisthina Atikah; Safrika (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
Oil palm (Elaeis guineensis Jacq.) is an oil-producing plantation crop that is a source of non-oil and gas foreign exchange in Indonesia This research was conducted in October-November 2022, the location of this research was carried out in the Batee Puteh plantation, Afdeling 1, West Aceh Regency. The data used in this study used primary data and secondary data. The sampling technique in this study used the saturated sampling method, which is a sampling technique when all populations are used as samples. The results of the data questionnaire were first carried out Validity Test, Normality Test and Multicollinearity Test. The analysis used in this research is multiple linear regression analysis to determine the relationship and influence of harvest premiums (Y) on work quality (X1), work quantity (X2), and attendance (X3). The results showed that the factors that influence the harvest premium on PT ASN oil palm harvest employees based on the t test table 0.05 (1.692) showed an influence on the variable X1 work quantity, X2 work quality where t count was smaller than the table. While the X3 attendance variable does not show an influence where t count is greater than t table. Based on the regression output, the R2 value is 0.622, meaning that the effect of the harvest premium can be explained well through the regression model built in this research by 62.2%.